The topology of non-resonant stellarator divertors - Robert Davies; Christopher B. Smiet; Alkesh Punjabi; Allen H. Boozer; Sophia A. Henneberg (Nuclear Fusion)
We apply topological methods to better understand how the magnetic field in the stellarator edge can be diverted away from the confined region. Our primary method is calculating the winding numbers of closed contours, which gives information on the number and nature of fixed points within a bounded region. We first apply this to the non-resonant divertor Hamiltonian system, and present a simple explanation for the system’s diversion: trajectories are guided away from the confined region by X-points which are ‘unpaired’ i.e. do not have corresponding O-points and therefore do not resemble an island chain. We show how similar phenomena can occur in a similar, axisymmetric Hamiltonian system. Secondly, we find examples of neoclassically optimised stellarators in the quasi-symmetric stellarator repository database which divert the magnetic field via unpaired X-points. We present and discuss three examples, each containing novel phenomena which might be desirable for stellarator divertors. These examples serve as an illustration of new divertor possibilities which exist in realistic stellarators, which may ultimately have application for future experiments and reactors.